Décoder à travers les âges: traduction polonaise des textes d’ancien français - Giermak-Zielińska, Teresa (Studia Romanica Posnaniensia, 2007)
The main problem discussed is how a contemporary Polish reader is supposed to receive a translation of a medieval text. The traditional choice between a philological translation and a stylistically enhanced text is not relevant according to the E. Nida’s theory of the dynamic equivalence. In his translation theory, special emphasis is given to the achievement of good readability. Some solutions resulting from author's practical experiences are proposed.